Changing Contact Patterns Over Disease Progression: Nipah Virus as a Case Study. (2nd March 2020) - Lee, Kyu Han; Nikolay, Birgit; Sazzad, Hossain M S; Hossain, M Jahangir; Khan, A K M Dawlat; Rahman, Mahmudur; Satter, Syed Moinuddin; Nichol, Stuart T; Klena, John D; Pulliam, Juliet R C; Kilpatrick, A Marm; Sultana, Sharmin; et al.
Abstract: Contact patterns play a key role in disease transmission, and variation in contacts during the course of illness can influence transmission, particularly when accompanied by changes in host infectiousness. We used surveys among 1642 contacts of 94 Nipah virus case patients in Bangladesh to determine how contact patterns (physical and with bodily fluids) changed as disease progressed in severity. The number of contacts increased with severity and, for case patients who died, peaked on the day of death. Given transmission has only been observed among fatal cases of Nipah virus infection, our findings suggest that changes in contact patterns during illness contribute to risk of infection. Abstract : We examined whether contact patterns change as disease progresses. For Nipah virus case patients identified between 2010 and 2014 in Bangladesh, the number of contacts increased with disease severity and, for patients who died, peaked on the day of death.